PENGEMBALIAN ASET TINDAK PIDANA KORUPSI PELAKU DAN AHLI WARISNYA MENURUT SISTEM HUKUM INDONESIA - Haswandi Haswandi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
National development and improving standards of living will be increasingly difficult to achieve if the level of corruption is high. Therefore, it is necessary seriousness in its eradication, either through criminal law as well as through the civil law against the perpetrators of corruption and to the heirs. For that we need strict laws governing asset recovery corruption of the perpetrators and their heirs as part of participating jointly responsible for restoring the proceeds of corruption to the state. The main problem in this dissertation research is about the law of return on assets How does the conception of corruption by the offender and his heirs? The method used in this research is normative juridical method using qualitative data analysis with content analysis techniques. Based on the results, it can be concluded: First, the laws of corruption in recovering assets from corruption cases at this time is not perfect because only put money substitute against corruption proceeds of crime from the perpetrator. Meanwhile, the civil law norms materilnya against the heirs of the perpetrators of corruption has not been set. Second, the existence of Article 33 and Article 34 of Law No. 31 of 1999 just a gate that the heirs of the perpetrators of corruption can be sued if the perpetrator as the heir of the heir died while either not return the results to the state of corruption. It is necessary to formulate norms for about an unlawful act which can be used as a legal basis to sue the heirs of the offender. Third, the legal concepts in asset recovery corruption perpetrators and the survivors of the Indonesian legal system should be directed to the improvement of legislation to prosecute not only the perpetrators but also heirs of the perpetrators of corruption.Keyword: corruption, aset recovery, heir